Clinical and biochemical aspects associated with diabetic nephropathy among type 2 diabetic males in Gaza strip - Abu Mustafa, Ayman; Yassin, Maged (International Journal of Medicine, 2017)
Background: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease, and the published data on various aspects of the disease is rare in Gaza Strip.Objective: to investigate clinical and biochemical aspects associated with DN among type 2 diabetic males in Gaza Strip.Methods: The study comprised 150 type 2 diabetic males from Gaza Strip. Data were obtained from a questionnaire interview, patients’ records, and biochemical analysis of blood and urine samples. Statistical analysis was performed using SPSS version 23.Results: The prevalence of DN was 71/150 (47.3%). Duration of diabetes in patients with DN was significantly higher than in patients without DN (p<0.001). Smoking, retinopathy, cardiovascular diseases (CVD) and neuropathy were significantly more frequent among patients with DN (p<0.05). Serum glucose, urea, creatinine, cholesterol and low-density lipoprotein cholesterol (LDL-C) were significantly higher, whereas high-density lipoprotein cholesterol (HDL-C) was significantly lower in patients with DN (p<0.05). Urinary albumin and Albumin/creatinine ratio (ACR) were 10 to 13 times higher in patients with DN. Conversely, glomerular filtration rate (GFR) was significantly lower in patients with DN (137.1±35.0 versus 187.8±70.8 ml/min/1.73m2, p<0.001). ACR showed significant positive correlations with duration of diabetes (r=0.311, p<0.001), glucose (r=0.308, p<0.001), urea (r=0.474, p<0.001), creatinine (r=0.356, p<0.001), cholesterol (r=0.307, p<0.001), LDL-C (r=0.319, p<0.001) and urinary albumin (r=0.942, p<0.001), and significant negative correlation with GFR (r=-0.297, p<0.001). The predicted factors of DN were duration of diabetes, smoking, retinopathy, CVD, neuropathy, glucose, urea, creatinine, cholesterol, LDL-C and GFR. The more to fewer effective predicted variables of ACR were urinary albumin, urea, creatinine, LDL-C, duration of diabetes, glucose, cholesterol and GFR.Conclusion: Management of some predicted factors of DN could delay the progression of the disease.